Ostraka Varia : tax receipts and legal documents on Demotic, Greek, and Greek-Demotic Ostraka, chiefly of the early Ptolemaic period, from various collections (P.L. Bat. 26) - Vleeming, S. P. (Papyrologica Lugduno-Batava;, 1994)
A large majority of the 65 ostraka published in this volume come from Egypt in the Third Century B.C. Some thirty are from Elephantine; these comprise a number of Greek and Greek-demotic receipts. Not unimportant new texts from Hermonthis and Thebes (among others, a fine example of a temple oath) add notably to the diversity of the volume. Although of course tax receipts predominate, these are present in a rich variety, and their commentaries add much to our knowledge of fiscal matters in this period. As a nouveauté the Greek and demotic texts are published on exactly the same footing, and a constant effort is made to merge the separate worlds of Greek and demotic papyrology. Hand-facsimiles facilitate the consultation of the individual texts; the whole is rounded off by photographic plates showing all texts in full.